2021
DOI: 10.1177/0734242x20987895
|View full text |Cite
|
Sign up to set email alerts
|

Process development options for electronic waste fractionation to achieve maximum material value recovery

Abstract: Revised legislation and bans on imports of waste electrical and electronic equipment (WEEE) into many Asian countries for treatment are driving the need for more efficient WEEE fractionation in Europe by expanding the capacity of treatment plants and improving the percentage recovery of materials of economic value. Data from a key stakeholder survey and consultation are combined with the results of a detailed literature survey to provide weighted matrix input into multi-criteria decision analysis calculations … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 62 publications
1
1
0
Order By: Relevance
“…From surveys with recyclers, the authors also concluded that recyclers need to develop better solutions in the phase of dismantling devices to improve the recovery performance of valuable materials. The same is claimed by Bruch et al (2021) through interviews with recyclers. New solutions to sorting materials and other pre-extractive techniques lack research (only 10.8%, as aforementioned).…”
Section: Recyclingsupporting
confidence: 62%
“…From surveys with recyclers, the authors also concluded that recyclers need to develop better solutions in the phase of dismantling devices to improve the recovery performance of valuable materials. The same is claimed by Bruch et al (2021) through interviews with recyclers. New solutions to sorting materials and other pre-extractive techniques lack research (only 10.8%, as aforementioned).…”
Section: Recyclingsupporting
confidence: 62%
“…The use of recycling processes results in tremendous energy and CO 2 -emission savings [63]. An overview of existing sorting and sensing technologies and requirements for WEEE recycling can be found in [64].…”
Section: ) Metalsmentioning
confidence: 99%
“…The main research methods in the work include: comparison of indicators, data analysis, generalization, and horizontal and vertical analysis. This study uses annual time series data covering the period from 2013-2021 [4][5][6].…”
Section: Introductionmentioning
confidence: 99%